2022
DOI: 10.3389/fonc.2021.835889
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib Plus Camrelizumab With/Without Chemoembolization for Hepatocellular Carcinoma: A Real-World Experience of a Single Center

Abstract: ObjectiveThis study was conducted in order to compare the efficacy and safety of transarterial chemoembolization (TACE) plus apatinib plus camrelizumab (TACE+AC) and apatinib plus camrelizumab (AC) in the treatment of unresectable hepatocellular carcinoma (HCC) in a real-world setting.MethodsIn this single-center retrospective study, the data of patients with unresectable HCC who had received TACE+AC or AC treatment during March 2017 to May 2021 were assessed. Patients in the AC group received intravenous admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 30 publications
9
44
0
Order By: Relevance
“…Ju et al. ( 39 ) found that TACE+apatinib+camrelizumab provided a clinical benefit for the subgroups of age <65 years old, men, PS score of 1, Child–Pugh classification of B, liver cirrhosis, hepatitis B infection, and AFP >200 mg/ml (all P<0.05), and similar findings were observed in the study of Zheng et al. ( 33 ).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Ju et al. ( 39 ) found that TACE+apatinib+camrelizumab provided a clinical benefit for the subgroups of age <65 years old, men, PS score of 1, Child–Pugh classification of B, liver cirrhosis, hepatitis B infection, and AFP >200 mg/ml (all P<0.05), and similar findings were observed in the study of Zheng et al. ( 33 ).…”
Section: Discussionsupporting
confidence: 70%
“…PFS at 0.5, 1, 1.5, and 2 years were evaluated in 13 ( 21 , 25 , 31 38 , 40 42 ), 13 ( 21 , 25 , 31 38 , 40 42 ), 11 ( 21 , 25 , 31 37 , 41 , 42 ), and 5 studies ( 21 , 32 , 34 , 37 , 42 ), and the pooled rates and 95%CI were 0.781 (0.688-0.862), 0.387 (0.293-0.486), 0.117 (0.076-0.165), and 0.069 (0.005-0.182), respectively ( Table 3 ). OS at 0.5, 1, 1.5, 2, and 3 years were evaluated in 12 ( 21 , 25 , 31 36 , 39 42 ), 12 ( 21 , 31 34 , 39 42 ), 12 ( 21 , 31 34 , 39 42 ), 9 ( 21 , 31 34 , 39 42 ), and 5 studies ( 21 , 31 33 , 42 ), and the pooled rates and 95%CI were 0.943 (0.902-0.975), 0.690 (0.585-0.786), 0.385 (0.246-0.533), 0.212 (0.117-0.324), and 0.056 (0.028-0.091), respectively ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall mPFS and mOS were significantly longer than those found in other retrospective studies involving apatinib (mPFS: 7.0 vs. 5.0 months; mOS: 16.0 vs. 13.0 months), especially as a second-line treatment; this may be due to the combination with immunotherapy (mOS: 14.0 months; mPFS: 8.0 months) or TACE (mOS: 20.0 months; mPFS: 11.0 months) in some patients in this study ( Zhen et al, 2018 ; Qin et al, 2021 ). In a recent single-center retrospective study about unresectable HCC, apatinib plus camrelizumab demonstrated the mOS of 13.1 months, which was similar to our results (14.0 months) ( Ju et al, 2021 ). Similar to other studies, apatinib combined with TACE significantly improved mPFS and mOS.…”
Section: Discussionsupporting
confidence: 90%
“…Jiang et al have found that metformin triggers the NF-κB signal pathway, which leads to caspase-3/GSDME-mediated cancer cell death [48]. Many recent attempts to increase effectiveness by combining TACE and targeted treatment with immunotherapy have been documented [49][50][51][52]. As a local chemotherapy modality, TACE can promote better immunotherapy by modulating the TIME [50].…”
Section: Discussionmentioning
confidence: 99%